Is it Possible to Quantify the Functions of the Dress? a question for functional analysis methods indesign (ModaPalavra e-periódico, 2020)
When we face the study of dress from its artifactual identity,we observe that its so-called functional dimension cannot beunderstood in the same terms proposed by the ergonomicsof the product, that is, from the ergonomic concepts ofusability, efficiency, effectiveness and psychological comfortin relation to a specific activity or work.This article, presents the results of a review of the functionalanalysis methods commonly used by design for the study ofclothing, and explains whythey are insufficient or limited toaddress the multiple functions of this particular artifact. Atthe same time, it proposes some considerations for itsfunctional analysis that contribute in a decisive way to thedesign process of the clothing design.
Keywords: clothing design; unctional analysis methods; clothed-body